CRUCIAL MARKERS SHOWING THE RISK OF CORONARY ARTERY DISEASE IN OBESITY: ADMA AND NEOPTERIN - Avci, Emre; Karabulut, Alpaslan; Alp Avci, Gulcin; Baba, Burcu; Bilgi, Cumhur (Journal of Medical Biochemistry, 2020)
Background: Obesity is responsible for high morbidity and mortality, both in developed and developing countries. It is associated with many chronic and metabolic diseases. Asymmetric dimethylarginine (ADMA) has been demonstrated to be a biomarker of endothelial dysfunction in humans and increased ADMA associated with cardiovascular disease (CVD) risk has been reported in many states. Neopterin (NP) produced by monocytes/macrophages in response to stimulation by interferon-gamma (IFN-g) is emphasized in recent findings. The current study aims to investigate ADMA and NP levels which may assume a role in guiding the early diagnosis of coronary artery disease in obesity. Methods: This is an original research study in which ADMA and NP levels of 50 patients (25 male/25 female) diagnosed with obesity were compared with those of 30 healthy individuals (15 male/15 female) as control. The high-performance liquid chromatography (HPLC) method was used while determining parameters. Results: ADMA and NP levels in obese individuals were found to be significantly higher than in those enrolled in the control. ADMA values were found to be higher in obese subjects (0.71±0.24 mmol/L) as compared with levels found in healthy subjects (0.58±0.16 mmol/L) (p<0.05). A significant increase of serum neopterin levels was found in obese subjects (8.8±3.5 mmol/L) as compared with controls (4.9±1.69 mmol/L) (p<0.05). Also, there was a strong positive correlation between NP and ADMA values in obese individuals (r=0.954). Conclusions: Our study revealed that obese subjects have higher ADMA and neopterin levels. These results demonstrated that both ADMA and NP levels may be potential risk factors for coronary heart disease in obesity.